The Effect Of Power Defined By Speed On The Development of Some Static And Fundamental Skills In Soccer For Junior Students - Abbas, Mofq (Journal of Physical Education, 2016)
The effect of Strength in Speed for Developing Dribbling The ball and kicking the ball The players of College of physical Education. The research consist five chapters, The lest chapter contain The definition, The problem, aims, hypothecs and finally The fields. The 2nd chapter cantinas The Strength and Speed and Dribbling The ball and kicking the ball developing basic skills in soccer Then The researcher Takes The Basic skills especially controlling and bribing drills. The third chapter include research method and field process. The sample of research was from soccer school That belong to Iraqi soccer federation also The pilot study was hailed and The post Test Then The main experiment. The fourth chapter consist display and analyzing research results which received and knowing developing of Basic skills.cast The fifth chapter contains conclusions and recommendation, also The Research contains geostationary and several attaches and paper of resources.